Ice Blocks from Norway The Importation of Natural Ice to Britain, Circa 1870-1925 - Freeman, Michael (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
For over fifty years, between around 1870 and 1914, there was a thriving trade that saw translucent block ice exported to Great Britain from the fjords and lakes of Norway. By 1899, the volume of ice landed in Britain had reached over half a million tons, with the port of London often accounting for 40-50 per cent of that total. The ice was needed for food preservation as Britain's increasingly urban and industrial population grew exponentially over the later nineteenth century and, over time, to satisfy Britons' taste for iced drinks and ice cream. For Norway, the trade yielded economic benefits across coastal communities of the south and south-east. In effect, ice production was a form of agriculture that gave rise to a regular labour force, multiple ice stores, and ingenious wooden chutes for moving ice blocks down to loading wharves. Ice Blocks from Norway: The Importation of Natural Ice to Britain, Circa 1870-1925 is a richly illustrated, definitive account of the history of this unique trade. The book will appeal to general, informed readers as well as academic specialists.